1978
DOI: 10.1172/jci108912
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Accumulation and Intracellular Binding of Conjugated Bilirubin

Abstract: A B S T R A C T After the intravenous injection of un

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 30 publications
0
37
1
3
Order By: Relevance
“…The hepatic uptake of bilirubin and BSP is rapid. After the intravenous injection of tracer amounts of [3H]bilirubin or [35S]BSP in rats, -40% of injected radioactivity is present within the liver 1.5 min later (2,(4)(5)(6). In the isolated perfused rat liver, 30 '251-albumin is injected simultaneously, all 1251 is recovered in the hepatic vein effluent confirming that albumin does not accompany bilirubin or BSP into the liver cell (7,8).…”
Section: Introductionmentioning
confidence: 83%
“…The hepatic uptake of bilirubin and BSP is rapid. After the intravenous injection of tracer amounts of [3H]bilirubin or [35S]BSP in rats, -40% of injected radioactivity is present within the liver 1.5 min later (2,(4)(5)(6). In the isolated perfused rat liver, 30 '251-albumin is injected simultaneously, all 1251 is recovered in the hepatic vein effluent confirming that albumin does not accompany bilirubin or BSP into the liver cell (7,8).…”
Section: Introductionmentioning
confidence: 83%
“…BR, however, is not a substrate for glutathione conjugation. The binding to GSTs reduces the efflux of BR from hepatocytes increasing its net uptake (Kamisaka et al, 1975;Wolkoff et al, 1978Wolkoff et al, , 2012. BR is then converted into mono-and di-glucuronide predominantly by a single uridine diphosphoglucuronate glucuronosyltransferase (UGTs) isoform, UGT1A1 (Bosma et al, 1994).…”
Section: Bilirubin Metabolismmentioning
confidence: 99%
“…While both strains are widely used in drug metabolism studies, strain characteristics might explain differences in responsiveness to certain inducing agents. For example, differences in glutathione S-transferase activity (GST) may alter net uptake of BR by hepatocytes (Wolkoff et al, 1978(Wolkoff et al, , 2012Higgins and Hayes, 2011). Furthermore, it has been reported that DBA/2 mice lack functional…”
Section: Cyp2a5 Overexpressing Microsomes Have Increased Br Degradatimentioning
confidence: 99%
“…Bilirubin is rapidly removed from the circulation and enters the hepatocyte, where it is conjugated with glucuronic acid and excreted into bile (3,4). Albumin does not enter the hepatocyte but remains in the circulation (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%